E-HERITAGE SEMARANG CULTURAL AS THE EFFORTS THE DOCUMENTATION DIGITAL PRESERVATION CULTURAL IN CENTRAL JAVA (Publikasi Eksternal, 2013)
Electronic Heritage (eHeritage) is a form of cultural legacy product documentation (analog) into digital format. Designing electronic-Heritage (eHeritage) in the form of digital documentation of cultural Heritage Semarang done to preserve one of the culture in central Java through the application of computer technology for the preservation and publication.Semarang cultural heritage in the form of digital documentation was made because it is one unique town, there are 101 ancient buildings / historic sites in the city of Semarang are still to be protected, where many of the amount was being torn down by the owner, or damage, and subject to change functions. So it is necessary to store information about cultural heritage as one of the cultures in Central Java, as the nation's cultural heritage.The final result of this research is the digital documentation of historical objects obtained from field surveys, results of on-line digital objects existing which has been uploaded and Documentation is done using Cloud Computing technology. Electronic Heritage (eHeritage) is a form of cultural legacy product documentation (analog) into digital format. Designing electronic-Heritage (eHeritage) in the form of digital documentation of cultural Heritage Semarang done to preserve one of the culture in central Java through the application of computer technology for the preservation and publication. Semarang cultural heritage in the form of digital documentation was made because it is one unique town, there are 101 ancient buildings / historic sites in the city of Semarang are still to be protected, where many of the amount was being torn down by the owner, or damage, and subject to change functions. So it is necessary to store information about cultural heritage as one of the cultures in Central Java, as the nation's cultural heritage. The final result of this research is the digital documentation of historical objects obtained from field surveys, results of on-line digital objects existing which has been uploaded and Documentation is done using Cloud Computing technology.